Method for testing bending rigidity of two-dimensional nano material
By combining theoretical calculation and big data analysis testing methods, the problem of low bending stiffness measurement accuracy in the prior art is solved, and higher measurement accuracy and reliability are achieved.
Patent Information
- Application Number
- CN202411444470.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has low accuracy when measuring the bending stiffness of two-dimensional nanomaterials, mainly because the traditional mechanical model is a pure theoretical model and lacks practical data support.
A test method combining theoretical calculation and big data analysis was adopted to form nanovacuoles through liquid-assisted wet transfer technology, and morphological analysis was performed using atomic force microscope. Combining the in-plane stiffness, number of layers and energy parameters of the nanovacuoles, a mechanical model was established to calculate the bending stiffness.
By combining theory and practical data, the measurement accuracy of bending stiffness of two-dimensional nanomaterials is improved, errors are reduced, and more reliable test results are provided.
Smart Images

Figure CN119534926A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of two-dimensional nanomaterials, and in particular to a method for testing the bending stiffness of two-dimensional nanomaterials. Background Art
[0002] Two-dimensional nanomaterials such as graphene, hexagonal boron nitride (hBN), molybdenum disulfide (MoS2), etc., due to their unique physical and chemical properties, have shown broad application prospects in electronic devices, energy storage, sensors and other fields. However, due to the particularity of nanoscale materials, the accurate measurement of their bending stiffness has always been a technical challenge. Traditional testing methods mostly rely on classical thin plate theory, but this method has low accuracy at the nanoscale.
[0003] In order to solve the above problems, after searching, a Chinese patent publication number CN112798822B discloses a test method for the bending stiffness of a two-dimensional nanomaterial and the interfacial adhesion energy between the two-dimensional nanomaterial and a substrate, comprising: adhering the two-dimensional nanomaterial to the surface of a first substrate, transferring the two-dimensional nanomaterial to the surface of a second substrate, and obtaining nanobubbles; performing morphological analysis on the nanobubbles according to a shape function to obtain undetermined parameter values in the shape function; analyzing the nanobubbles according to the undetermined parameter values in the shape function in combination with a mechanical model to obtain the bending stiffness of the two-dimensional nanomaterial.
[0004] The above patent has the following deficiencies: it uses shape functions combined with mechanical models for analysis, but its mechanical model is a purely theoretical model, and errors may occur in actual calculations, resulting in low accuracy.
[0005] To this end, the present invention proposes a method for testing the bending stiffness of two-dimensional nanomaterials Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a testing method for the bending stiffness of two-dimensional nanomaterials.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for testing the bending stiffness of a two-dimensional nanomaterial comprises the following steps:
[0009] S1: Sample preparation, selection of 2D nanomaterials, and adhesion of 2D nanomaterials to the substrate surface;
[0010] S2: Transfer and nanobubble formation: Using liquid-assisted wet transfer technology, the two-dimensional nanomaterial is transferred from one substrate to another substrate. During the transfer process, nanobubbles will form under the two-dimensional nanomaterial due to the interface effect between the two-dimensional nanomaterial and the second substrate.
[0011] S3: morphological analysis, using atomic force microscopy to perform morphological analysis on the nanobubble, obtain the projection radius a of the nanobubble, the height h of the center point of the upper surface relative to the substrate surface, and the distance r between the test point and the projection of the center point of the upper surface of the nanobubble on the plane where the second substrate surface is located, and describe the morphology through shape function;
[0012] S4: Calculation of bending stiffness: Based on the shape function, combined with the in-plane stiffness E2D of a single-layer two-dimensional nanomaterial, the number of layers N of the two-dimensional nanomaterial, and the energy Δγ parameter required per unit area of nanobubbles, a mechanical model is established to calculate the bending stiffness D.
[0013] Preferably: in step S1, the two-dimensional nanomaterial is graphene, the material thickness is 1-100 nm, and the sheet diameter is 10-200 μm.
[0014] Preferably: in the steps S1 and S2, the substrate is a rigid substrate or a flexible substrate.
[0015] Preferably, the rigid substrate is a silicon wafer, a metal wafer, a glass wafer or a sapphire substrate.
[0016] Preferably, the flexible substrate is any one of a polymethyl methacrylate substrate, an epoxy resin substrate, a polystyrene substrate, a polydimethylsiloxane substrate, a polyurethane substrate, a polyamide elastomer substrate or a polyolefin elastomer substrate.
[0017] Preferably: in the step S1, the adhesion method is a micromechanical peeling method, a chemical vapor deposition method or an epitaxial growth method.
[0018] Preferably: in step S3, the shape function is w(r)=f(r, a, h), and f is a known function form.
[0019] Preferably: in the step S4, the mechanical model is D=g(a, h, E2D, N, Δγ), where g is a known function.
[0020] Preferably, in step S3, g is determined by combining previous data with curve fitting, which specifically includes the following steps:
[0021] S31: Obtain known big data and perform morphological analysis on the two-dimensional nanomaterial with bending stiffness D;
[0022] S32: Use the morphological analysis as the abscissa and the bending stiffness as the ordinate to establish a two-dimensional coordinate system;
[0023] S33: selecting a plurality of two-dimensional nanomaterials with different bending stiffnesses in the big data, repeating step S32, forming a plurality of coordinate points in the coordinate system, and connecting adjacent coordinate points with smooth curves to form a test performance curve;
[0024] S34: Fitting the bending stiffness curve to obtain a function expression of the curve, which is g. In the step S33, the curve fitting is performed in the form of Taylor series expansion, that is, where g (n) (T0) is the nth derivative of g(T) at T0, and n! is the factorial of n.
[0025] Preferably: in the step S43, R n (T) is the error function, Where a∈(T0,T) or a∈(T,T0).
[0026] The beneficial effects of the present invention are:
[0027] 1. The present invention adopts theoretical calculation for the mechanical model, uses big data to obtain the relationship between the independent variable and the stiffness, and then uses curve fitting to finally form the mechanical model, thereby combining theory with practice and increasing accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a flow chart of a method for testing the bending stiffness of two-dimensional nanomaterials proposed in the present invention. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods.
[0030] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", and "set" should be understood in a broad sense, for example, they can be fixedly connected or set, or detachably connected or set, or integrally connected or set. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0031] Embodiment 1:
[0032] A method for testing the bending stiffness of a two-dimensional nanomaterial comprises the following steps:
[0033] S1: Sample preparation, selection of 2D nanomaterials, and adhesion of 2D nanomaterials to the substrate surface;
[0034] S2: Transfer and nanobubble formation: Using liquid-assisted wet transfer technology, the two-dimensional nanomaterial is transferred from one substrate to another substrate. During the transfer process, nanobubbles will form under the two-dimensional nanomaterial due to the interface effect between the two-dimensional nanomaterial and the second substrate.
[0035] S3: morphological analysis, using atomic force microscopy to perform morphological analysis on the nanobubble, obtain the projection radius a of the nanobubble, the height h of the center point of the upper surface relative to the substrate surface, and the distance r between the test point and the projection of the center point of the upper surface of the nanobubble on the plane where the second substrate surface is located, and describe the morphology through shape function;
[0036] S4: Calculation of bending stiffness: Based on the shape function, combined with the in-plane stiffness E2D of a single-layer two-dimensional nanomaterial, the number of layers N of the two-dimensional nanomaterial, and the energy Δγ parameter required per unit area of nanobubbles, a mechanical model is established to calculate the bending stiffness D.
[0037] In the step S1, the two-dimensional nanomaterial is graphene, the material thickness is 1 nm, and the sheet diameter is 10 μm.
[0038] In the steps S1 and S2, the substrate is a rigid substrate.
[0039] The rigid substrate is a silicon wafer.
[0040] In the step S1, the adhesion method is a micromechanical peeling method, a chemical vapor deposition method or an epitaxial growth method.
[0041] In step S3, the shape function is w(r)=f(r, a, h), where f is a known function form.
[0042] In step S4, the mechanical model is D=g(a, h, E2D, N, Δγ), where g is a known function.
[0043] In the step S3, g is determined by combining previous data with curve fitting, which specifically includes the following steps:
[0044] S31: Obtain known big data and perform morphological analysis on the two-dimensional nanomaterial with bending stiffness D;
[0045] S32: Use the morphological analysis as the abscissa and the bending stiffness as the ordinate to establish a two-dimensional coordinate system;
[0046] S33: selecting a plurality of two-dimensional nanomaterials with different bending stiffnesses in the big data, repeating step S32, forming a plurality of coordinate points in the coordinate system, and connecting adjacent coordinate points with smooth curves to form a test performance curve;
[0047] S34: Fitting the bending stiffness curve to obtain a function expression of the curve, which is g. In the step S33, the curve fitting is performed in the form of Taylor series expansion, that is, where g (n) (T0) is the nth derivative of g(T) at T0, and n! is the factorial of n.
[0048] In the step S43, R n (T) is the error function, Where a∈(T0,T) or a∈(T,T0).
[0049] Embodiment 2:
[0050] A method for testing the bending stiffness of a two-dimensional nanomaterial comprises the following steps:
[0051] S1: Sample preparation, selection of 2D nanomaterials, and adhesion of 2D nanomaterials to the substrate surface;
[0052] S2: Transfer and nanobubble formation: Using liquid-assisted wet transfer technology, the two-dimensional nanomaterial is transferred from one substrate to another substrate. During the transfer process, nanobubbles will form under the two-dimensional nanomaterial due to the interface effect between the two-dimensional nanomaterial and the second substrate.
[0053] S3: morphological analysis, using atomic force microscopy to perform morphological analysis on the nanobubble, obtain the projection radius a of the nanobubble, the height h of the center point of the upper surface relative to the substrate surface, and the distance r between the test point and the projection of the center point of the upper surface of the nanobubble on the plane where the second substrate surface is located, and describe the morphology through shape function;
[0054] S4: Calculation of bending stiffness: Based on the shape function, combined with the in-plane stiffness E2D of a single-layer two-dimensional nanomaterial, the number of layers N of the two-dimensional nanomaterial, and the energy Δγ parameter required per unit area of nanobubbles, a mechanical model is established to calculate the bending stiffness D.
[0055] In the step S1, the two-dimensional nanomaterial is graphene, the material thickness is 1-100 nm, and the sheet diameter is 10-200 μm.
[0056] In the steps S1 and S2, the substrate is flexible.
[0057] The flexible substrate is a polymethyl methacrylate substrate.
[0058] In the step S1, the adhesion method is chemical vapor deposition.
[0059] In step S3, the shape function is w(r)=f(r, a, h), where f is a known function form.
[0060] In step S4, the mechanical model is D=g(a, h, E2D, N, Δγ), where g is a known function.
[0061] In the step S3, g is determined by combining previous data with curve fitting, which specifically includes the following steps:
[0062] S31: Obtain known big data and perform morphological analysis on the two-dimensional nanomaterial with bending stiffness D;
[0063] S32: Use the morphological analysis as the abscissa and the bending stiffness as the ordinate to establish a two-dimensional coordinate system;
[0064] S33: selecting a plurality of two-dimensional nanomaterials with different bending stiffnesses in the big data, repeating step S32, forming a plurality of coordinate points in the coordinate system, and connecting adjacent coordinate points with smooth curves to form a test performance curve;
[0065] S34: Fitting the bending stiffness curve to obtain a function expression of the curve, which is g. In the step S33, the curve fitting is performed in the form of Taylor series expansion, that is, where g (n) (T0) is the nth derivative of g(T) at T0, and n! is the factorial of n.
[0066] In the step S43, R n (T) is the error function, Where a∈(T0,T) or a∈(T,T0).
[0067] Embodiment 3:
[0068] A method for testing the bending stiffness of a two-dimensional nanomaterial comprises the following steps:
[0069] S1: Sample preparation, selection of 2D nanomaterials, and adhesion of 2D nanomaterials to the substrate surface;
[0070] S2: Transfer and nanobubble formation: Using liquid-assisted wet transfer technology, the two-dimensional nanomaterial is transferred from one substrate to another substrate. During the transfer process, nanobubbles will form under the two-dimensional nanomaterial due to the interface effect between the two-dimensional nanomaterial and the second substrate.
[0071] S3: morphological analysis, using atomic force microscopy to perform morphological analysis on the nanobubble, obtain the projection radius a of the nanobubble, the height h of the center point of the upper surface relative to the substrate surface, and the distance r between the test point and the projection of the center point of the upper surface of the nanobubble on the plane where the second substrate surface is located, and describe the morphology through shape function;
[0072] S4: Calculation of bending stiffness: Based on the shape function, combined with the in-plane stiffness E2D of a single-layer two-dimensional nanomaterial, the number of layers N of the two-dimensional nanomaterial, and the energy Δγ parameter required per unit area of nanobubbles, a mechanical model is established to calculate the bending stiffness D.
[0073] In the step S1, the two-dimensional nanomaterial is graphene, the material thickness is 1-100 nm, and the sheet diameter is 10-200 μm.
[0074] In the steps S1 and S2, the substrate is a rigid substrate or a flexible substrate.
[0075] The rigid substrate is a silicon wafer, a metal wafer, a glass wafer or a sapphire substrate.
[0076] The flexible substrate is any one of a polymethyl methacrylate substrate, an epoxy resin substrate, a polystyrene substrate, a polydimethylsiloxane substrate, a polyurethane substrate, a polyamide elastomer substrate or a polyolefin elastomer substrate.
[0077] In the step S1, the adhesion method is a micromechanical peeling method, a chemical vapor deposition method or an epitaxial growth method.
[0078] In step S3, the shape function is w(r)=f(r, a, h), where f is a known function form.
[0079] In step S4, the mechanical model is D=g(a, h, E2D, N, Δγ), where g is a known function.
[0080] In the step S3, g is determined by combining previous data with curve fitting, which specifically includes the following steps:
[0081] S31: Obtain known big data and perform morphological analysis on the two-dimensional nanomaterial with bending stiffness D;
[0082] S32: Use the morphological analysis as the abscissa and the bending stiffness as the ordinate to establish a two-dimensional coordinate system;
[0083] S33: selecting a plurality of two-dimensional nanomaterials with different bending stiffnesses in the big data, repeating step S32, forming a plurality of coordinate points in the coordinate system, and connecting adjacent coordinate points with smooth curves to form a test performance curve;
[0084] S34: Fitting the bending stiffness curve to obtain a function expression of the curve, which is g. In the step S33, the curve fitting is performed in the form of Taylor series expansion, that is, where g (n) (T0) is the nth derivative of g(T) at T0, and n! is the factorial of n.
[0085] In the step S43, R n (T) is the error function, Where a∈(T0,T).
[0086] Embodiment 4:
[0087] A method for testing the bending stiffness of a two-dimensional nanomaterial comprises the following steps:
[0088] S1: Sample preparation, selection of 2D nanomaterials, and adhesion of 2D nanomaterials to the substrate surface;
[0089] S2: Transfer and nanobubble formation: Using liquid-assisted wet transfer technology, the two-dimensional nanomaterial is transferred from one substrate to another substrate. During the transfer process, nanobubbles will form under the two-dimensional nanomaterial due to the interface effect between the two-dimensional nanomaterial and the second substrate.
[0090] S3: morphological analysis, using atomic force microscopy to perform morphological analysis on the nanobubble, obtain the projection radius a of the nanobubble, the height h of the center point of the upper surface relative to the substrate surface, and the distance r between the test point and the projection of the center point of the upper surface of the nanobubble on the plane where the second substrate surface is located, and describe the morphology through shape function;
[0091] S4: Calculation of bending stiffness: Based on the shape function, combined with the in-plane stiffness E2D of a single-layer two-dimensional nanomaterial, the number of layers N of the two-dimensional nanomaterial, and the energy Δγ parameter required per unit area of nanobubbles, a mechanical model is established to calculate the bending stiffness D.
[0092] In the step S1, the two-dimensional nanomaterial is graphene, the material thickness is 1-100 nm, and the sheet diameter is 10-200 μm.
[0093] In the steps S1 and S2, the substrate is a rigid substrate or a flexible substrate.
[0094] The rigid substrate is a silicon wafer, a metal wafer, a glass wafer or a sapphire substrate.
[0095] The flexible substrate is any one of a polymethyl methacrylate substrate, an epoxy resin substrate, a polystyrene substrate, a polydimethylsiloxane substrate, a polyurethane substrate, a polyamide elastomer substrate or a polyolefin elastomer substrate.
[0096] In the step S1, the adhesion method is a micromechanical peeling method, a chemical vapor deposition method or an epitaxial growth method.
[0097] In step S3, the shape function is w(r)=f(r, a, h), where f is a known function form.
[0098] In step S4, the mechanical model is D=g(a, h, E2D, N, Δγ), where g is a known function.
[0099] In the step S3, g is determined by combining previous data with curve fitting, which specifically includes the following steps:
[0100] S31: Obtain known big data and perform morphological analysis on the two-dimensional nanomaterial with bending stiffness D;
[0101] S32: Use the morphological analysis as the abscissa and the bending stiffness as the ordinate to establish a two-dimensional coordinate system;
[0102] S33: selecting a plurality of two-dimensional nanomaterials with different bending stiffnesses in the big data, repeating step S32, forming a plurality of coordinate points in the coordinate system, and connecting adjacent coordinate points with smooth curves to form a test performance curve;
[0103] S34: Fitting the bending stiffness curve to obtain a function expression of the curve, which is g. In the step S33, the curve fitting is performed in the form of Taylor series expansion, that is, where g (n) (T0) is the nth derivative of g(T) at T0, and n! is the factorial of n.
[0104] In the step S43, R n (T) is the error function, Where a∈(T,T0).
[0105] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for testing the bending stiffness of two-dimensional nanomaterials, characterized in that: The following steps are involved: S1: Sample preparation, selection of 2D nanomaterials, and adhesion of 2D nanomaterials to the substrate surface; S2: Transfer and nanobubble formation: Using liquid-assisted wet transfer technology, the two-dimensional nanomaterial is transferred from one substrate to another substrate. During the transfer process, nanobubbles will form under the two-dimensional nanomaterial due to the interface effect between the two-dimensional nanomaterial and the second substrate. S3: morphological analysis, using atomic force microscopy to perform morphological analysis on the nanobubble, obtain the projection radius a of the nanobubble, the height h of the center point of the upper surface relative to the substrate surface, and the distance r between the test point and the projection of the center point of the upper surface of the nanobubble on the plane where the second substrate surface is located, and describe the morphology through shape function; S4: Calculation of bending stiffness: Based on the shape function, combined with the in-plane stiffness E2D of a single-layer two-dimensional nanomaterial, the number of layers N of the two-dimensional nanomaterial, and the energy Δγ parameter required per unit area of nanobubbles, a mechanical model is established to calculate the bending stiffness D.
2. The method for testing the bending stiffness of a two-dimensional nanomaterial according to claim 1, characterized in that: In the step S1, the two-dimensional nanomaterial is graphene, the material thickness is 1-100 nm, and the sheet diameter is 10-200 μm.
3. The method for testing the bending stiffness of a two-dimensional nanomaterial according to claim 1, characterized in that: In the steps S1 and S2, the substrate is a rigid substrate or a flexible substrate.
4. The method for testing the bending stiffness of a two-dimensional nanomaterial according to claim 3, characterized in that: The rigid substrate is a silicon wafer, a metal wafer, a glass wafer or a sapphire substrate.
5. The method for testing the bending stiffness of a two-dimensional nanomaterial according to claim 3, characterized in that: The flexible substrate is any one of a polymethyl methacrylate substrate, an epoxy resin substrate, a polystyrene substrate, a polydimethylsiloxane substrate, a polyurethane substrate, a polyamide elastomer substrate or a polyolefin elastomer substrate.
6. The method for testing the bending stiffness of a two-dimensional nanomaterial according to claim 1, characterized in that: In the step S1, the adhesion method is a micromechanical peeling method, a chemical vapor deposition method or an epitaxial growth method.
7. The method for testing the bending stiffness of a two-dimensional nanomaterial according to claim 1, characterized in that: In step S3, the shape function is w(r)=f(r, a, h), where f is a known function form.
8. The method for testing the bending stiffness of a two-dimensional nanomaterial according to claim 1, characterized in that: In step S4, the mechanical model is D=g(a, h, E2D, N, Δγ), where g is a known function.
9. The method for testing the bending stiffness of a two-dimensional nanomaterial according to claim 1, characterized in that: In the step S3, g is determined by combining previous data with curve fitting, which specifically includes the following steps: S31: Obtain known big data and perform morphological analysis on the two-dimensional nanomaterial with bending stiffness D; S32: Use the morphological analysis as the abscissa and the bending stiffness as the ordinate to establish a two-dimensional coordinate system; S33: selecting a plurality of two-dimensional nanomaterials with different bending stiffnesses in the big data, repeating step S32, forming a plurality of coordinate points in the coordinate system, and connecting adjacent coordinate points with smooth curves to form a test performance curve; S34: Fitting the bending stiffness curve to obtain a function expression of the curve, which is g. In the step S33, the curve fitting is performed in the form of Taylor series expansion, that is, where g (n) (T0) is the nth derivative of g(T) at T0, and n! is the factorial of n.
10. A method for testing the bending stiffness of a two-dimensional nanomaterial according to claim 9, characterized in that: In the step S43, R n (T) is the error function, Where a∈(T0,T) or a∈(T,T0).
Citation Information
Patent Citations
A method for testing the bending stiffness of two-dimensional nanomaterials and their interfacial adhesion energy with a substrate.
CN112798822B